Analisis Aliran Daya Reconductoring Saluran Transmisi Paiton Kraksaan-Probolinggo 150 kV Terhadap Saluran Yang Terimbas - Rohmanita Duanaputri; Ahmad Hermawan; Zulvina Arifah (UPT - P2M POLINEMA, 2022)
Provision of quality and sufficient electrical energy is something that must be done by PT. PLN (Persero). Based on data from PT. PLN (Persero), carried out work on replacing conductors on the Paiton – Kraksaan – Probolinggo transmission line from the TACSR 330 mm2 conductor with KHA 1190 A to 2xACCC/TW Copenhagen with KHA 2016 A. Reconductoring work is one of the efforts to uprating the transmission line by considering increasing load requirements. This reconductoring is carried out using the open circuit method or a total blackout in a circuit where the conductor is being replaced by taking into account the stages determined by PT. PLN (Persero). So that the power flow in the system must be considered when these conditions take place for the sake of service reliability or system reliability using a power flow simulator application, namely ETAP software. The simulation voltage tolerance with actual conditions is 5%. Next, analyze the power flow on the affected transmission line which is directly connected to the Kraksaan – Paiton – Probolinggo 150 kV transmission line based on voltage drop, transmission line losses and loading from each stage. As well as calculating the power transfer capability after and before reconductoring. The results of the simulation show that the most significant anomaly (deviation that should not be) is that there is a critical point loading of up to 89.220% on the Probolinggo - Gondangwetan channel when reconductoring has been carried out except for the Paiton - Kraksaan1 transmission line. Meanwhile, the value of power transfer capability increased after reconductoring, where the Paiton-Kraksaan1 and Paiton-Kraksaan2 channels increased by 63.91 MW, the Kraksaan - Probolinggo1 channel increased by 67.95 MW, and the Kraksaan - Probolinggo2 channel increased by 63.461 MW from previously